2016
DOI: 10.1128/iai.00189-16
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Analysis Reveals that the 2010 Haiti Cholera Epidemic Is Linked to a Hypervirulent Strain

Abstract: bVibrio cholerae O1 El Tor strains have been responsible for pandemic cholera since 1961. These strains have evolved over time, spreading globally in three separate waves. Wave 3 is caused by altered El Tor (AET) variant strains, which include the strain with the signature ctxB7 allele that was introduced in 2010 into Haiti, where it caused a devastating epidemic. In this study, we used phenotypic analysis to compare an early isolate from the Haiti epidemic to wave 1 El Tor isolates commonly used for research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 48 publications
1
37
0
5
Order By: Relevance
“…Although the causes of the V. cholerae O1 population shift from classical to El Tor biotypes are not clearly understood, loss of H-NS in El Tor biotype V. cholerae mimics an evolutionary backward change. A recent study of wave 3 El Tor O1 strains isolated during the 2010 cholera outbreak in Haiti revealed that these isolates, which express elevated CT and hemolysin compared to earlier wave 1 strains, harbored mutations in the hns gene [45]. This finding highlights the importance of H-NS transcriptional silencing and antirepression in pathogen evolution.…”
Section: H-ns Transcriptional Silencing and Anti-silencingmentioning
confidence: 99%
“…Although the causes of the V. cholerae O1 population shift from classical to El Tor biotypes are not clearly understood, loss of H-NS in El Tor biotype V. cholerae mimics an evolutionary backward change. A recent study of wave 3 El Tor O1 strains isolated during the 2010 cholera outbreak in Haiti revealed that these isolates, which express elevated CT and hemolysin compared to earlier wave 1 strains, harbored mutations in the hns gene [45]. This finding highlights the importance of H-NS transcriptional silencing and antirepression in pathogen evolution.…”
Section: H-ns Transcriptional Silencing and Anti-silencingmentioning
confidence: 99%
“…These strains have spread globally in three separate waves [3]. While acquiring numerous changes in their genetic background, wave 3 altered El Tor (AET) strains have propagated through many of the cholera endemic regions in Asia and Africa [4]. After the 2010 earthquake in Haiti, a disastrous cholera outbreak emerged in late October which affected over 600,000 people, resulting in deaths of around 8000 Haitians [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular c-di-GMP levels vary in different V. cholerae isolates [7]. Thus, when tested in different V. cholerae genetic backgrounds, additional DGCs and PDEs were shown to govern motility.…”
Section: Introductionmentioning
confidence: 99%